Optimization of Traffic Education by the Kamsel Unit to Improve Traffic Awareness in the Kendal Police Resort - Suyuthi, Taufiqurrahman (Advances in Police Science Research Journal, 2024)
The Kendal Regency, with its dense and high-speed traffic dominated by two-wheeled vehicles, prompted the Kamsel Unit of the Kendal Police Traffic Unit to make efforts to increase traffic awareness through Traffic Education. This article aims to explain how the management of the Kendal Police Traffic Unit utilizes Traffic Education to improve traffic awareness and how the organizational resources of the Kamsel Unit can help students in Kendal Regency to play a more active role in implementing Traffic Education. Observation, interviews, and document analysis are data collection methods used in qualitative research. The author analyzed the problem formulation in chapter I using communication theory, management theory, SWOT analysis theory, Traffic Education concept, optimization concept, and awareness concept in chapter II of the conceptual literature. The Optimization of Traffic Education by the Kamsel Unit to Improve Traffic Awareness in the Kendal Police Resort is the result of this final project research. However, there are still some shortcomings, such as inadequate planning due to the absence of school targets, suboptimal organizing because Kamsel Unit members have not implemented traffic law enforcement training, ineffective and inefficient implementation of Traffic Education due to less varied material, and the lack of Leadership Guidance and consolidation activities before and after Traffic Education activities as a form of member control. Based on the author's observations, the Kamsel Unit of the Kendal Police Traffic Unit should implement Traffic Education for all students, taking into account the organizational resources available and improving the management of the implementation of Traffic Education to fully realize its potential. By doing so, the number of traffic violations committed by students in Kendal Regency can be reduced.